Transforming growth factor β1 induction of vascular endothelial growth factor receptor 1: Mechanism of pericyte-induced vascular survival in vivo - Shih, Shu-Ching (National Academy of Sciences, 2003)
Degeneration of vessels precedes and precipitates the devastating ischemia of many diseases, including retinopathy of prematurity and diabetic retinopathy. Ischemia then leads to proliferative retinopathy and blindness. Understanding the mechanisms of blood vessel degeneration is critical to prevention of these diseases. Vessel loss is associated with oxygen-induced suppression of vascular endothelial growth factor (VEGF) and with pericyte (vascular smooth muscle cell) dropout. The molecular mechanism of pericyte protection of the vasculature is unknown. We show that transforming growth factor β1 (TGF-β1)-expressing pericytes are specifically found on vessels resistant to oxygen-induced loss. TGF-β1 potently induces VEGF receptor 1 (VEGFR-1) expression in endothelial cells and thereby prevents oxygen-induced vessel loss in vivo. Vessel survival is further stimulated with a VEGFR-1-specific ligand, placental growth factor 1. TGF-β1 induction of VEGFR-1 in endothelial cells explains pericyte protection of vessels and the selective vulnerability of neonatal vessels to oxygen. These results implicate induction and activation of VEGFR-1 as critical targets to prevent vessel loss.